2022
DOI: 10.3390/cryst12040545
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Cu/ZSM-5 Catalysts Synthesized by Two Ion-Exchange Methods

Abstract: As catalysis is one of the pillars of green chemistry, this work aimed at continuing the development of synthesized catalysts under controlled conditions that allow the attainment of materials with the best physicochemical properties for the process for which they were designed. Based on this, the synthesis, characterization, and comparison of copper-based catalysts supported on ammonium and acidic ZSM-5-type zeolite by two ion exchange methods, liquid phase and solid state, are presented. The catalysts obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…More in detail, Cu 10 ZSM5_WI distinctly shows two peaks at 2θ=35.5° and 38.7°, while sample Cu 5 ZSM5_WI is characterised only by the weak peak at 38.7°, due to the formation of bulky CuO at the external surface of the zeolite particles [39] . Contrary, the other catalysts do not present these diffraction lines, so copper could be considered to be located within the pores and channels of the parent zeolite, after it was exchanged for the proton, forming a metal complex inside the channels that cannot be detected via XRD [40,41] …”
Section: Resultsmentioning
confidence: 96%
“…More in detail, Cu 10 ZSM5_WI distinctly shows two peaks at 2θ=35.5° and 38.7°, while sample Cu 5 ZSM5_WI is characterised only by the weak peak at 38.7°, due to the formation of bulky CuO at the external surface of the zeolite particles [39] . Contrary, the other catalysts do not present these diffraction lines, so copper could be considered to be located within the pores and channels of the parent zeolite, after it was exchanged for the proton, forming a metal complex inside the channels that cannot be detected via XRD [40,41] …”
Section: Resultsmentioning
confidence: 96%
“…It is well known that the preparation methods of catalysts have significant influences on the catalytic performances, which mainly include coprecipitation [22,23,49], impregnation [47,70,71], and sol-gel [65,70,72]. However, to further enhance the activity, selectivity, water tolerance, and stability of Cu-based catalysts, some emerging methods have appeared in recent reports [25,46,50,73,74].…”
Section: Preparation Methodsmentioning
confidence: 99%
“…SiO 2 is widely used as a support for various heterogeneous catalysts due to its low price and high specific surface area. For instance, Shawabkeh et al [65] studied the CO 2 adsorption on SiO 2 at different Cu loading to investigate the CO 2 interaction with the surface (mainly oxygen atom) via the sol-gel method from both experimental and theoretical points of view. The results suggested that an increase in the amount of CuO on the surface of SiO 2 improved the basicity of the adsorbent, resulting in more CO 2 uptake.…”
Section: Supportsmentioning
confidence: 99%